The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1253/circj.cj-14-1352
|View full text |Cite
|
Sign up to set email alerts
|

The Leipzig Prospective Drug-Eluting Balloon-Registry – Outcome of 484 Consecutive Patients Treated for Coronary In-Stent Restenosis and De Novo Lesions Using Paclitaxel-Coated Balloons –

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp in DES is associated with worse outcomes than with ISR in BMS. 13 Currently, there is no clear consensus about the optimal management of ISR. Intracoronary stenting is still the preferred treatment in patients with ISR after DES or BMS implantation. 9,14-16 However, drug-eluting balloons (DEB) provide potential advantages: 17 rapid release of high drug concentrations and homogeneous drug delivery to the vessel wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…16 The incidence of cardiac death was 1.8% in our cohort, which is consistent with DCB safety outcome concluded from other DCB studies. 17,18 Previous DCB trials have reported low MI rates at long period follow-up. 18,19 This is comparable to the 2.4% incidence of MI in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…16 The incidence of cardiac death was 1.8% in our cohort, which is consistent with DCB safety outcome concluded from other DCB studies. 17,18 Previous DCB trials have reported low MI rates at long period follow-up. 18,19 This is comparable to the 2.4% incidence of MI in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five percent received bailout BMS implantation which was not associated with a less favorable outcome (MACE 7.1% with additional BMS and 9.5% without BMS) [41]. The prospective Leipzig Registry evaluated the clinical outcome in 484 patients treated with a SeQuent Please DEB [42]. De novo vessel disease was seen in 76 patients (15.7%).…”
Section: Drug-eluting Balloonsmentioning
confidence: 99%
“…In de novo lesions, no TLR was seen after 27 months. MACE was defined differently than in other studies and was thus difficult to compare [42]. Being the second largest real world registry, the SeQuent Please Small Vessel “PCB Only” Registry was a prospective multicenter study assessing the safety and efficacy of the SeQuent Please DEB in 447 patients [35].…”
Section: Drug-eluting Balloonsmentioning
confidence: 99%
“…Patients with blocked coronary arteries undergoing PCI are given the choice to receive either drug‐eluting stents (DESs) or bare metal stents (BMSs) to restore the normal blood flow. Currently, bare metal stents have ≈30% chance of restenosis occurring within a six‐month period . Long‐term metallic stents may also interfere with computer tomography (CT) and magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%
“…A complete degradation period for polymer based stents including poly‐ l ‐lactic acid (PLLA) and poly‐ l ‐caprolactone (PCL) have been reported as ca. two years while for polyglycolic acid were found to be 6–12 months . An ideal period for stent degradation would finally depend on the targeted disease with requirement of small or longer time interventions.…”
Section: Introductionmentioning
confidence: 99%